PO51 | Thrombocythemia associated with a non-canonical JAK2 mutation: a case report (Bleeding, Thrombosis and Vascular Biology)
Background: Myeloproliferative neoplasms (MPNs) are hematologic malignancies marked by clonal myeloid proliferation in the bone marrow. Common genetic drivers include JAK2-V617F, JAK2 exon 12, MPL, and CALR mutations. However, some patients with myelofibrosis (MF) or essential thrombocythemia (ET) are “triple negative,” likely due to non-canonical mutations, as seen in the following case.